RBM15-mediated m6A modification in cancer progression and tumor immunity: molecular mechanisms and therapeutic potential - Li, Chunhong; Jiang, Xiulin; Yuan, Yixiao; Wang, Qiang (Frontiers in Cell and Developmental Biology, 2025)
RBM15, a key RNA-binding protein involved in m6A RNA methylation, plays multifaceted roles in cancer development and tumor immunity. Emerging evidence indicates that RBM15 regulates tumor cell proliferation, migration, invasion, and metabolic reprogramming through modulation of RNA stability, splicing, and translation. Beyond its tumor-intrinsic effects, RBM15 influences the tumor immune microenvironment by affecting immune cell differentiation, activation, and cytokine production, thereby contributing to immune evasion. Dysregulated RBM15 expression has been observed across various cancer types, correlating with poor prognosis and therapy resistance. These findings highlight RBM15 as a promising biomarker for cancer diagnosis and prognosis and suggest its potential as a therapeutic target. Future studies focusing on RBM15-targeted interventions, either alone or in combination with immunotherapy, may provide novel strategies for precision cancer treatment.